QUALITY OF PUBLIC SERVICES IN ISSUING CERTIFICATES OF INDIGENCE AT THE KAWEDUSAN VILLAGE OFFICE - Ridha Amrullah , Ahmad; Nuryanti; Sutowo (Universitas Islam Balitar, 2024)
This study discusses the quality of public service in the issuance of certificates of indigence at the Kawedusan Village Office, Ponggok District, Blitar Regency. The quality of public service can be measured using five dimensions: tangible, reliability, responsiveness, assurance, and empathy. The research was conducted from March to May 2024. This study employs a descriptive method with a qualitative approach, using data collection techniques such as observation, interviews, documentation, and data analysis through triangulation. Informants were selected using purposive sampling. The findings of this study indicate that the quality of public service in the issuance of certificates of indigence (SKTM) at the Kawedusan Village Office meets the tangible dimension, as evidenced by the availability of service tools such as computers and printers, as well as a clean and comfortable service area. The reliability dimension is met through the staff's ability to operate service tools and maintain good service quality standards. The responsiveness dimension is demonstrated by quick, accurate, and responsive service. The assurance dimension is fulfilled by timely service guarantees and service legality assurance. The empathy dimension is evidenced by the friendly, polite, and respectful attitude of the staff in providing service, valuing each applicant who comes in, and prioritizing the applicant's needs. This research highlights the importance of internet-based programs such as electronic queuing systems and online service applications to enhance efficiency and accuracy in service delivery.